The anti-HIV-1 activity of polyphenols from Phyllanthus urinaria and the pharmacokinetics and tissue distribution of its marker compound, gallic acid - Xiaoxue Zhang; Qing Xia; Guanghui Yang; Dan Zhu; Yanyan Shao; Jiaying Zhang; Yaping Cui; Rufeng Wang; Lanzhen Zhang (Journal of Traditional Chinese Medical Sciences, 2017)
Objective: To investigate the in vitro anti-HIV-1 activities and its associated mechanism of action of an extract isolated from Phyllanthus urinaria (P. urinaria) and to develop an HPLC test method for detecting gallic acid (GA) in plasma and tissues to study its pharmacokinetics and tissue distribution in rats. Methods: An extract of P. urinaria was isolated and purified by phytochemistry and chromatography techniques. The anti-HIV-1 activities and toxicities of the extract and its component GA were determined in human T lymph cells (MT-4) by the MTT method. The mechanism of its anti-HIV-1 action was studied to examine the in vitro binding of its components with HIV-1 target proteins by Biacore technique. The pharmacokinetics and tissue distribution of GA were investigated after oral administration of polyphenol extract (PE) and pure GA in rats. The concentrations of GA in plasma and tissues were determined by HPLC. Results: The PE and GA isolated from P. urinaria had anti-HIV-1 activities with IC50s of 0.61 μg/mL and 0.76 μg/mL, respectively. The Biacore study indicated that PE and GA interacted with HIV-1 RT, gp120, and P24. The pharmacokinetic parameters Tmax, Cmax, AUC0–t, and T1/2 for GA were (60.0 ± 3.0) minutes, (2.87 ± 0.50) μg·mL−1, (343.5 ± 11.2) mg·min·L−1, and (113.3 ± 9.3) minutes while the parameters for GA in the PE were (10.0 ± 1.3) minutes, (3.89 ± 0.90) μg·mL−1, (394.7 ± 14.0) mg·min·L−1, and (81.7 ± 4.1) minutes, respectively. GA was detected in rat lungs, liver, kidneys, heart and spleen. Conclusion: A PE isolated from P. urinaria containing GA has anti-HIV-1 activities. GA is quickly absorbed and slowly eliminated in rats after oral administration. The pharmacokinetics of GA administered as a PE is desirable, and it is widely distributed in the main tissues of lung and liver. Both its properties and anti-HIV-1 activities make it of interest for further studies.